Customer satisfaction evaluation and recommendations for a marketing communication. Case: Business-Hotel “Karelia” - Guterman, Yana (Mikkelin ammattikorkeakoulu, 2015)
The economic which crisis started at the end of 2014 in Russia affected the hospitality industry significantly, the amount of tourists decreased, and issues of customer satisfaction and new cus-tomers’ attraction have become very important for hotel businesses. The main objectives of this thesis were to evaluate the current level of customer satisfaction and suggest some new ways of communication with the potential customers for the Business-Hotel “Karelia”. This hotel, located in Saint-Petersburg made a request for research for a better under-standing of the current problems in the service. First of all, the literature review was done for the determination of a theoretical background about customer satisfaction, its aspects and measurement methods. Also marketing communications in the hospitality industry and their planning principles were described in detail. Furthermore, three types of research methods were used: quantitative research was conducted in the hotel and via Internet, two semi-structured interviews were carried out with the managers of the hotel and the hotel restaurant, and finally electronic research was done as a supporting method. Some significant results were produced on the basis of a thorough analysis of the theoretical and empirical data. These results helped to formulate several conclusions about the general level of satisfaction and discovered the reasons of customer dissatisfaction. The main reasons were con-nected to the quality of the rooms and supplies, quality of the service itself, and some supporting services. Therefore, some recommendations were produced for the improvement of the customer satisfaction level. Moreover, most popular marketing communication channels were identified and suggestions for the marketing communications system development offered.